Diet and feeding in the Cape Cobra, Naja nivea. Issue 2 (3rd July 2017) - Layloo, Inshaaf; Smith, Caitlin; Maritz, Bryan
Abstract: It is widely reported that African cobras (genus Naja ) are generalist predators, but examination of formal literature yields relatively little evidence of this for most species. Here, we review the diet of cape cobras ( Naja nivea ) based on examination of museum specimens, an extensive literature review, and social media reported natural history observations. We quantify dietary niche breadth and test the hypothesis that cape cobras are generalist predators. Additionally, we test the hypotheses that diet varies significantly (1) across biomes, and (2) across winter, summer and year-round rainfall regions. We gathered 101 feeding records for cape cobras and based on family-level prey frequencies calculated Levins' measure of niche breadth as B = 6.57, which we standardised to B A = 0.29. We found no association between prey classes and biomes or rainfall region. Our data indicate that cape cobras consume a wide range of vertebrate prey from all four tetrapod classes, including a large number and diversity of snakes. Our findings suggest that cape cobras may be involved in several important ecological processes. Moreover, our study demonstrates the utility and value of collating natural history observations reported on social media platforms.